Development and Validation of Atomic Absorption Spectroscopic Method for Analysis of ZnO in Blemish Balm Cream - Sophi Damayanti (Science Faculty of Chiang Mai University, 2019)
Blemish balm cream is one of the recently famous cosmetics that are used by women in order to protect skin from UV radiation and give coverage at the same time. Zinc oxide acts as an active sunscreen agent in BB Cream by refracting and absorbing UV rays to prevent skin cancer and damage of other organs. However, ZnO has the ability to penetrate skin and enter the bloodstream and may cause skin side effects such as photosensitization. Therefore the maximum concentration of ZnO in sunscreen that stated by FDA is only up to 25 percent. The purposes of the present study are to develop and validate an analytical method for determination of ZnO in cosmetic preparations by using Atomic Absorption Spectroscopy (AAS) and to apply the method to the samples from various market origins. Recommended parameters of Zn metal measurement were Hollow Cathode Lamp (operating current 7.0 mA), wavelength at 213.9 nm, air-acetylene flame, and slit width of 1.0 nm. Linearity of Zn standard solution showed a good correlation with linear equation was y = 0.054x + 0.0571, regression coefficient (R2) was 0.9993 and VX0 was 1.59. Limit of Detection was determined in a value 0.314 mg/mL whereas Limit of Quantification was 0.952 mg/mL. The Coefficient Variant of precision test was 0.99% and 1.09% for intraday and interday respectively. Accuracy was shown in terms of percentage recovery that lies in a range of 100.85-102.56%. Dry and wet digestion method was done on Standard Reference Material and placebo cream. % CV for intra- and inter-day precision for dry digestion were 1.86% and 2.33%, respectively, whereas those of wet digestion were 1.18% and 1.39%, respectively. The percentage recoveries for dry and wet digestion were 95.51-98.72% and 99.57-101.03% respectively. Statistical analysis using paired t-test showed that both methods differ significantly. Hence eleven samples of marketed products were digested using wet digestion method. Results of total percentage of ZnO in the samples were in the range of 0.48-6.55%. This AAS method fulfills validation criteria and could be developed to determine ZnO in the samples.